Emerging Technology in Urban Areas of Developing Countries for Sustainable Wastewater Treatment and Reuse - Jhansi, Dr. Seetharam Chittoor; Mishra, Dr. Santosh Kumar (Consilience, 2013)
In order to achieve ecological wastewater treatment, a “closed-loop treatment system” is recommended. Many present day systems are a “disposal-based linear system”. The traditional linear treatment systems must be transformed into the cyclical treatment to promote the conservation of water and nutrient resources. Using organic waste nutrient cycles, from “point-of-generation” to “point-of-production”, closes the resource loop and provides an approach for the management of valuable wastewater resources. Failing to recover organic wastewater from urban areas means a huge loss of life-supporting resources that instead of being used in agricultural for food production, fill rivers with polluted water. The development of ecological wastewater management strategies will contribute to the reduction of pathogens in surface and groundwater to improve public health. The objective of present paper is to give an insight into the appropriate technology for treatment of wastewater. The paper discusses sustainable wastewater treatment systems in the context of urban areas of the developing world. The paper concludes that “since the urban areas of many developing countries are growing rapidly, ecological sanitation systems must be implemented that are sustainable and have the ability to adapt and grow with the community’s sanitation needs”. In order to decide what the appropriate treatment system is, the developer must consider the area’s climate, topography, and socioeconomic factors.